El archivo del monasterio de Canonesas del Santo Sepulcro: Historia y características: Architecture of the church of Saint Nicholas and the monastery of Holy Sepulchre, from the reconquest of Saragossa to the 19th century. - Gutiérrez Gutiérrez, Manuel D. (Artigrama, 2025)
ResumenEl archivo de una institución religiosa es una fuente fundamental para el conocimiento histórico de esta a la vez que un patrimonio de valor incalculable. En el presente artículo se presenta la historia del Archivo del Monasterio de Canonesas del Santo Sepulcro de Zaragoza desde la fundación de la comunidad, su conservación por las canonesas, la puesta en valor y situación actual. Por último, se comentan algunos aspectos de interés para los investigadores del arte.AbstractThe archive of a religious institution is a fundamental source for the historic knowledge and an invaluable legacy. In this article we present the history of the Monastery of Canonnesses of Holy Sepulchre of Saragossa archive’s since the foundation of the community, the conservation work by the canonnesses, the promotion of heritage and the contemporary situation of the documents. At last, we discuss some aspects of interest of the archive for artistic research.KeywordsArchives, Monastery, Canonesses, Holy Sepulchre, Conservation, Inventory, Documentation.
Keywords: Archivos; Monasterio; Canonesas; Santo Sepulcro; Conservación; Inventario; Documentación